DETERMINANTS OF PROFITABILITY: EVIDENCE FROM INFRASTRUCTURE SECTOR ON INDONESIA STOCK EXCHANGE - Fayad Setiawan; Sunita Dasman (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to investigate the effects of corporate growth, leverage, and size on profitability. The two primary ideas that make up the theoretical framework are signaling theory and trade-off theory. This kind of study employs a quantitative approach, which entails processing data as numerical values. This study uses secondary data that was obtained from the Indonesia Stock Exchange's official website. 69 infrastructure-related businesses that are listed on the Indonesia Stock Exchange make up the study's population. This study's sampling strategy combines purposive sampling with non-probability sampling, in which the samples are chosen according to predetermined standards. Forty-five firms were utilized as samples in this investigation. Using Eviews 12 software, panel data regression is the data analysis method utilized in this study. Descriptive statistical analysis, partial hypothesis testing, traditional assumption testing, and determination coefficient keys are all examples of data analysis testing. The study's findings suggest that, business size has no discernible effect on profitability. Profitability is significantly impacted, by debt and business expansion.